High Carriage Rates of Multidrug-Resistant Gram-Negative Bacteria in Neonatal Intensive Care Units From Ghana. (28th March 2020) - Labi, Appiah-Korang; Bjerrum, Stephanie; Enweronu-Laryea, Christabel C; Ayibor, Prosper K; Nielsen, Karen L; Marvig, Rasmus L; Newman, Mercy J; Andersen, Leif P; Kurtzhals, Jorgen A L
Abstract: Background: Carriage of multidrug resistant (MDR) Gram-negative bacteria (GN) in hospitalized neonates may increase the risk of difficult-to-treat invasive infections at neonatal intensive care units (NICUs). Data on MDRGN carriage among hospitalized newborns in Africa are limited. Methods: We conducted a cross-sectional study at the NICUs of 2 tertiary hospitals in Ghana. Swabs from the axilla, groin, perianal region, and the environment were cultured, GN were identified, and antibiotic susceptibility was tested. We obtained blood culture isolates from neonates with sepsis. Whole-genome sequencing was used to characterize carbapenemase-producing Klebsiella pneumoniae . Typing was done by multilocus sequence typing (MLST) and single nucleotide polymorphism (SNP) analysis. Results: A total of 276 GN were isolated from 228 screened neonates. Pathogenic GN were cultured in 76.8% (175 of 228) of neonates. Klebsiella spp (41.7%; 115 of 276) and Escherichia coli (26.4%; 73 of 276) were the commonest organisms. Carriage rates of MDRGN and third-generation cephalosporin resistant organisms were 49.6% (113 of 228) and 46.1% (105 of 228), respectively. Among Klebsiella spp, 75.6% (87 of 115) phenotypically expressed extended-spectrum β-lactamase activity, whereas 15.6% expressed carbapenemase and harbored bla- OXA-181 and bla- CTX-M-15 . Overall, 7.0% (16 of 228) of neonates developed GN bloodstream infection. In 2 of 11 neonates, sequencing showed the same identity between carriage and the bloodstream isolate. Length of stay before specimen collection and antibiotic use were independently associated with carriage rates, which increased from 13% at admission to 42% by day 2 and reached a plateau at 91% by day 15. Conclusions: High carriage rates of MDRGN, including carbapenemase-producing enterobacterales may be an emerging problem in NICUs in Africa. Abstract : We show carriage rate of MDR enterobacterales among neonates in 2 NICUs in Ghana. MDR carriage is associated with duration of stay and antibiotic use. We also report OXA-181 carbapenemase-producing organism from Ghana. WGS showed identity between carriage and BSI.